White Middle-Class Men in Rio de Janeiro : the Making of a Dominant Subject. - Corossacz, Valeria Ribeiro (Latin American gender and sexualities., 2017)
This book analyzes experiences of upper-middle-class white men living in wealthy parts of Rio de Janeiro. The author investigates what it means to be classified as a white person and a man in a society that is known for its valorization of racial mixing and yet deeply structured by racism, class, and gender inequalities.